PERBANDINGAN PEMBERIAN INFORMED CONSENT SECARA VERBAL DENGAN PRESENTASI VIDEO TERHADAP PENGETAHUAN PROSEDUR ANESTESI UMUM INTUBASI PADA PASIEN YANG AKAN MENJALANI OPERASI - Roby; Lunarta Siahaan, Dwi; Tobing, Jerry (Jurnal Kedokteran Methodist, 2022)
Background : Informed consent was one of the basic consideration for doctors to took of medical actions to saved patients’ lives. Informed consent must be clearly given to the patient so that the patient understood the purpose of the medical action, procedure, risks, side effects, alternative actions and recovery period in certain conditions. Differences in ability and understanding information, an unwillingness to asked could make the purpose of provided information unattainable. This study aimed to compared the provision of informed consent verbal with video presentations on knowledge of general anesthesia procedures in patients who would undergo surgery Methods: This research used literature review. Data obtained from secondary data using a documentary technique. Data documentation based on journals relating to variable research.. Conclusion: There was a relationship between giving informed consent by video presentation to the knowledge of patients who will undergo surgery